2011
DOI: 10.1590/s1806-83242011000300008
|View full text |Cite
|
Sign up to set email alerts
|

Vimentin expression and the influence of Matrigel in cell lines of head and neck squamous cell carcinoma

Abstract: Vimentin is a cytoeskeletal intermediate filament protein commonly observed in mesenchymal cells; however, it can also be found in malignant epithelial cells. It is demonstrated in several carcinomas, such as those of the cervix, breast and bladder, in which it is widely used as a marker of the epithelial to mesenchymal transition that takes place during embryogenesis and metastasis. Vimentin is associated with tumors that show a high degree of invasiveness, being detected in invasion front cells. Its expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…We found that all markers were detectable in the 51 malignant PT specimens with the following frequencies among different patients: GD2 (100%, 51/51) CD166 (78.4%, 40/51), CD90 (78.4%, 40/51), CD44 (68.6%, 35/51), CD106 (29.4%, 15/51), CD29 (27.4%, 14/51) and CD105 (1.9%, 1/51) (Table 1). Vimentin was expressed in all tumor specimens, consistent with their mesenchymal lineage [25]. CD117 was expressed in 70.5% of the malignant PT specimens which is in line with the report of its expression in 13% and 67%, of benign and malignant PTs, respectively [26].…”
Section: Resultssupporting
confidence: 75%
“…We found that all markers were detectable in the 51 malignant PT specimens with the following frequencies among different patients: GD2 (100%, 51/51) CD166 (78.4%, 40/51), CD90 (78.4%, 40/51), CD44 (68.6%, 35/51), CD106 (29.4%, 15/51), CD29 (27.4%, 14/51) and CD105 (1.9%, 1/51) (Table 1). Vimentin was expressed in all tumor specimens, consistent with their mesenchymal lineage [25]. CD117 was expressed in 70.5% of the malignant PT specimens which is in line with the report of its expression in 13% and 67%, of benign and malignant PTs, respectively [26].…”
Section: Resultssupporting
confidence: 75%
“…De Araujo et al (1993) demonstrated that the expression of the Vimentin was most marked in oral squamous cell carcinoma with high tumour grade. Also, significant correlation between Vimentin expression and aggressive tumour features, including lymph node involvement, was recently shown by immunophenotypic analysis of the head and neck squamous cell carcinoma (Mandal et al , 2008; Dal Vechio et al , 2011). Our results did not indicate significant association between Vimentin expression and HPV infection.…”
Section: Discussionmentioning
confidence: 86%
“…Vimentin, an intermediate filament protein type, is associated with a high degree of invasiveness (45,46). It is considered that Matrigel can promote cell invasion of head and neck squamous cell carcinoma cells through increasing vimentin expression in vitro (47).…”
Section: Discussionmentioning
confidence: 99%